Hearing loss following spinal anaesthesia among obstetric patients at the University College Hospital Ibadan (2017)
Background: Sensorineural hearing loss (SNHL) is a rarely reported complication of subarachnoid block and may go unnoticed unless audiometric test is performed. Objective: The aim of this study was to determine the prevalence of sensorineural hearing loss following spinal anaesthesia in obstetric patients. Patients and Methods: Seventy patients of ASA physical status classes I and II scheduled for elective Caesarean section were randomized into two groups (A & B). Lumbar puncture was performed using 25 gaugepencil point spinal needle type in group A and 25 gauge Quincke cutting tip type in group B. Spinal anaesthesia was achieved in both groups with 12.5mg (2.5ml) of 0.5% hyperbaric bupivacaine subarachnoid injection in the sitting position. Each patient had a preoperative pure tone audiometry (PTA) test done before spinal anaesthesia as a baseline; this was repeated on the first and third days after the surgery for each patient. Results: Twelve (34.3%) patients in group A and 24 (68.6%) in group B had more than one attempt at lumbar puncture; and 5[1 (2.9%) from group A and 4 from group B (11.4%)] developed Post Dural Puncture Headache(PDPH), p= 0.36. Of the 4 patients in group B who developed PDPH, 2 had associated transient sensorineural hearing loss. Conclusion: This study shows that spinal anaesthesia may lead to transient hearing loss among few obstetric patients without long term sequelae. Use of Quincke spinal needle type was more likely to cause PDPH and transient hearing loss.